THE IMPACT OF IDEA MANAGEMENT SYSTEMS ON INTELLECTUAL RESOURCES DEVELOPMENT - Miķelsone, Elīna; Volkova, Tatjana; Spilbergs, Aivars; Liela, Elita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Topicality/Problem. Idea management systems (IMS) are manageable, systematic tools, tool kits or complex systems that helps to generate and evaluate ideas and are an important element of organizational development. Many well-known organizations (e.g. Volkswagen, Microsoft, GE Healthcare, Procter and Gamble, Boeing, Siemens, etc) are successfully applying web-based IMS. But there is no research that explores the impact of web-based IMS on intellectual resources development. Research aim – to research the impact of IMS on intellectual resources development and to provide recommendations to practitioners for its broader assistance in enterprises to ensure innovation acceleration. Methodological approach. The empirical research was based on 447 enterprise survey applying. The research results show the following results: IMS application has resulted in a new intellectual resource, in a patents and improved innovation acceleration.Research limitations. Survey research may limit the generalisability of the result, because the survey target group is commercially available web-based IMS applied enterprises.Originality/value. The research based on the empirical data analysis contributes to understanding the directions and significance of IMS impact on intellectual resources development.